A hospital based cross sectional study of acute pancreatitis with special reference to computed tomographic evaluation - M., Jyothi S.; Karpur, Santosh U. (International Journal of Advances in Medicine, 2018)
Background: All suspected cases of acute pancreatitis should undergo CT scan. It is non invasive and reliable. CT scan is able to give complete picture of acute pancreatitis. The objective of the present Methods: The present study was hospital based. 60 cases with evidence of acute pancreatitis were included. They were studied for 3 years from June 2015 to May 2018. CT scan was performed in all cases. CT features of the pancreas were noted and described. Results: Acute pancreatitis incidence was four times more in males compared to females i.e. 80% vs. 20%. CT scan showed that pancreatic gland was normal only in 16.7% of the cases. The contour was irregular in 66.7% of the cases. Eight cases showed necrosis. Less than 30% three patients (10%) had grade A acute pancreatitis. 28 cases were showing Phlegmonous changes. In 24 cases it was observed that lesser sac was affected. Conclusions: Authors conclude that for grading and staging of the pancreatitis of acute nature, CT scan is must and is very helpful to the clinicians. CT scan helps not only in precise diagnosis but also in predicting the proper prognosis of the patients who are affected by the pancreatitis of acute in nature.